Peran Subsektor Peternakan dalam Perekonomian Jawa Tengah - Rafsanjani, Roviki; Suhendarsyah, Suhendarsyah; Kristin, Silalahi Maria; Firman, Achmad (Universitas Galuh, 2025)
The livestock subsector is one of the main sectors in Indonesia's economy, contributing significantly to economic growth. Livestock farming in Central Java Province has experienced the fastest growth compared to other subsectors under the agricultural sector, such as food crops, horticulture, plantations, and agricultural services and hunting. The workforce involved in the livestock subsector also plays an important role in supporting economic growth. Business investment in a subsector is positively correlated with the labor absorbed in that subsector, making it essential for the government to implement strategic efforts and plans to enhance the region's potential for significant investment growth. This study aims to analyze the role of the livestock subsector in the economy of Central Java. The method used includes basic statistical analysis techniques, such as percentages, growth rates or trends, and comparisons. The statistical analysis results are described descriptively to provide explanations for the findings. The production of meat and milk in Central Java Province has shown a significant decrease, which is caused by PMK and LSD diseases as well as the economic impact of the post-COVID-19 pandemic. The population of beef cattle has experienced stable growth, but the population of other livestock such as goats and sheep has declined. The number of workers has also significantly decreased, possibly due to the PMK outbreak and the impact of the COVID-19 pandemic. Although the value of domestic investment (PMDN) experienced a drastic decrease in 2020, it has significantly increased in 2021 and 2022.